Analysis on topological features in spatial distribution pattern using GIS and remote sensing. (10th June 2022) - Li, Bingxin; Yu, Anbang; Liu, Tong; Guo, Sulin
Taking Antu, Dehui and the Tongyu city of Jilin Province as the typical county unit as research objects, using the data of Landsat8 remote sensing image and official survey map in 2018, the research extracted the scope of environmental constrain factors and agricultural land uses, as well as the geographical information of rural residents by human-computer interaction interpretation method. Then the spatial distribution pattern of rural settlement of Jilin province would be analysed respectively from morphological structure, environmental constrain and agricultural production perspectives with the help of GIS spatial analysis method. It is found that: the rural settlement was in radiating spatial distribution pattern along Ha-Chang urbanisation development belt in northeastern China on the whole and its density of Central > East > West of Jilin Province. And its spatial distribution pattern is obviously affected by radiation effect from road system and aggregation effect of orchards land.